Characterization of the novel HLA‐A*02:939 allele by sequencing‐based typing. (5th January 2021) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐A*02:939 differs from HLA‐A*02:01:01:01 by one nucleotide substitution in codon 222 in exon 4.